Analisis Pengamanan Aset Tanah Milik Pemerintah Daerah Melalui Sertipikasi Di Kota Tanjungbalai (Studi Pada Kantor Pertanahan Kota Tanjungbalai) - Simanjuntak, Adelina Pratiwi; Eddy, Triono; Limbong, Dayat (UNES Law Review, 2024)
The safeguarding of assets belonging to the Tanjungbalai city government through land certification. So on the plot of land it can be known with certainty the location of the land, the boundaries of the land, the area of the land, the buildings and the types of plants that are on it. Local governments in implementing their regional autonomy system will create good governance by making fundamental changes in the management and optimization of their resources. So that various affairs to the regional government which have been delegated the authority can be carried out optimally, one of which is the management of assets belonging to the local government of Tanjungbalai City. The problem in this study is to find out how to manage Tanjungbalai City government assets in the perspective of Law No. 1 of 2004 and Government Regulation No. 6 of 2006 and the efforts made by the Tajungbalai City government in securing land assets belonging to the region as well as the obstacles experienced by the City government. and the Tanjungbalai City Land Office. Based on research conducted at the Land Office of Tanjungbalai City and Tanjungbalai City Government, it was found that there was land that did not have rights as a result of the non-optimal work of the local government so that it gave positive changes to the assets of the Tanjungbalai city government.